The War against Ukraine, Europeanization, and Impact on Cultural Heritage Narratives in the Candidate Countries - HERȚA, Laura-Maria; CORPĂDEAN, Adrian (2024)
The volume brings together political scientists, historians,anthropologists and experts on international relations and thecultural ﻿patrimony of the countries envisaged, and groups togetheranalyses on the subject matter. The aim of the book is to rekindleinterest in the study of the preservation of the cultural ﻿patrimonyin the EU’s immediate neighbourhood. Methodological insights,as well as case analyses, are included in this volume.